In media(tization) studies we love metaphors - Scolari, Carlos A. (MATRIZes, 2023)
The long history of mass communication theories is full of metaphors, from Shannon and Weaver’s ‘transmission channel’ to Noelle-Neumann’s ‘spiral of silence’. The objective of the chapter is to give an overview of the use of metaphors and models in mediatized communication studies. Special attention is given to the metaphors that support the representations of digital and interactive communication practices; in this context, the chapter deals with the metaphors of the Internet, the World Wide Web, and new platforms and introduces the main metaphors of media change. The chapter concludes with a series of reflections on the risks and benefits of metaphorical reasoning and includes a call for ‘metaphorical experimentation’.